Endothelial heterogeneity in the response to autophagy drives small vessel muscularization in pulmonary hypertension - Zhang, Qi; Yaoita, Nobuhiro; Tabuchi, Arata; Liu, Shaofei; Chen, Shiau-Haln; Li, Qiuhua; Hegemann, Niklas; Li, Caihong; Rodor, Julie; Timm, Sara; Laban, Hebatullah; Finkel, Toren; et al. (Circulation, 2024)
BACKGROUND: - Endothelial cell (EC) apoptosis and proliferation of apoptosis-resistant cells is a hallmark of pulmonary hypertension (PH). Yet, why some ECs die and others proliferate and how this contributes to vascular remodeling is unclear. We hypothesized that this differential response may: (1) relate to different EC subsets, namely pulmonary artery (PAECs) versus microvascular ECs (MVECs); (2) be attributable to autophagic activation in both EC subtypes; and (3) cause replacement of MVECs by PAECs with subsequent distal vessel muscularization. - METHODS: - EC subset responses to chronic hypoxia were assessed by single-cell RNA sequencing of murine lungs. Proliferative versus apoptotic responses, activation, and role of autophagy were assessed in human and rat PAECs and MVECs, and in precision-cut lung slices of wild-type mice or mice with endothelial deficiency in the autophagy-related gene 7 (Atg7EN-KO). Abundance of PAECs versus MVECs in precapillary microvessels was assessed in lung tissue from patients with PH and animal models on the basis of structural or surface markers. - RESULTS: - In vitro and in vivo, PAECs proliferated in response to hypoxia, whereas MVECs underwent apoptosis. Single-cell RNA sequencing analyses support these findings in that hypoxia induced an antiapoptotic, proliferative phenotype in arterial ECs, whereas capillary ECs showed a propensity for cell death. These distinct responses were prevented in hypoxic Atg7EN-KO mice or after ATG7 silencing, yet replicated by autophagy stimulation. In lung tissue from mice, rats, or patients with PH, the abundance of PAECs in precapillary arterioles was increased, and that of MVECs reduced relative to controls, indicating replacement of microvascular by macrovascular ECs. EC replacement was prevented by genetic or pharmacological inhibition of autophagy in vivo. Conditioned medium from hypoxic PAECs yet not MVECs promoted pulmonary artery smooth muscle cell proliferation and migration in a platelet-derived growth factor-dependent manner. Autophagy inhibition attenuated PH development and distal vessel muscularization in preclinical models. - CONCLUSIONS: - Autophagic activation by hypoxia induces in parallel PAEC proliferation and MVEC apoptosis. These differential responses cause a progressive replacement of MVECs by PAECs in precapillary pulmonary arterioles, thus providing a macrovascular context that in turn promotes pulmonary artery smooth muscle cell proliferation and migration, ultimately driving distal vessel muscularization and the development of PH.